The Role of the Consistency Principle in Recognition of Income Method on the Income Statement at PT. Indo Zinc Diecasting in Gresik - Enny Istanti (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: to determine the role of the principle of consistency in the method of revenue recognition on the income statement. Design/methodology/approach: This research approach uses a descriptive method, which describes the actual situation that occurs in the company for analysis using the applicable theory. While in this study the method used by the author is to use a qualitative method Findings: This result affects the net profit obtained by the company because of the unrecorded income and expenses. From the evidence above, it can be seen that with the method of recognizing revenues and expenses at the time of sale and adjustments to revenues and expenses that have not been recognized, they can be presented fairly in the financial statements. Practical implications: intensify the recognition of revenues and expenses at the time of sale and adjustments for unrecognized revenues and expenses Originality/values: This paper is original Paper types: research sense